PENGARUH KERJASAMA TIM, SEMANGAT KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR BADAN PENGELOLAHAN KEUANGAN DAERAH (BPKD) PROVINSI BENGKULU - Dela Utari; Islamuddin Islamuddin (Yayasan Insani Mandiri Santani, 2022)
The purpose of this study was to determine the effect of teamwork, work spirit and work discipline on employee performance at the Bengkulu Province Regional Financial Management Agency.This research uses quantitative research methods using a descriptive approach . The population in this study were 46 employees at the Bengkulu Province Regional Financial Management Agency office with a total sample of 46 respondents and sampling using the total sampling method. Data collection techniques used in the form of observation, interviews and questionnaires. The data analysis technique used is in the form of data instrument testing (validity test and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), descriptive analysis, multiple linear regression, correlation coefficient analysis, coefficient of determination, hypothesis testing (test t and F test).Based on the results of multiple linear regression, the regression equation form Y = 2.767 + 0.962 X1 + 0.425 X2 + 0.545 X3. The results of the study and the hypothesis show that teamwork (X1) has a significant effect on employee performance (Y), tcount > ttable (9,027 > 2,016) and (sig <α = 0.000 < 0.050), work morale (X2) has a significant effect on employee performance ( Y), tcount > ttable (3.709 > 2.016) and (sig<α = 0.001 < 0.050)., Work discipline (X3) has a significant effect on employee performance (Y), tcount > ttable (4,713 > 2.016) and (sig<α = 0.000 < 0.050). Simultaneously Teamwork (X1), work spirit (X2) and work discipline (X3) have a significant effect on employee performance at the Bengkulu Province Regional Financial Management Agency Office. This result is evidenced by the f test which shows that among them Fcount > Ftable, namely (61.094 > 4.051 and (sig = 0.000 < 0.050).Keywords: Teamwork, Work Spirit, Work Discipline, Employee Performance.